2021
DOI: 10.1186/s12903-021-01988-0
|View full text |Cite
|
Sign up to set email alerts
|

Immediate restoration of fixed full-arch prostheses placed on implants in both fresh and healed sockets using the flat one-bridge technique: a 7-year retrospective study

Abstract: Background The aim of this retrospective study was to document the long-term clinical efficacy of a surgical-prosthetic technique (the flat one-bridge technique) involving the immediate restoration of both postextraction and nonpostextraction implants supporting full-arch restorations. Methods Implants were placed by adapting the axis to the available bone. Flat definitive abutments were connected during surgery and never disconnected to compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…In the present study, the mean marginal bone loss was 1.51 ± 1.16 mm after a 3.5-year follow-up. This marginal bone loss was higher than the results described in other clinical studies of immediate functional loading in fully edentulous patients with a full arch rehabilitation with a 6–9 years follow-up [ 24 , 39 , 40 ]. Smoking habits are an important risk factor for marginal bone loss in patients treated with the immediate functional loading of implants placed in periodontally compromised sites [ 8 , 23 , 41 ].…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…In the present study, the mean marginal bone loss was 1.51 ± 1.16 mm after a 3.5-year follow-up. This marginal bone loss was higher than the results described in other clinical studies of immediate functional loading in fully edentulous patients with a full arch rehabilitation with a 6–9 years follow-up [ 24 , 39 , 40 ]. Smoking habits are an important risk factor for marginal bone loss in patients treated with the immediate functional loading of implants placed in periodontally compromised sites [ 8 , 23 , 41 ].…”
Section: Discussioncontrasting
confidence: 59%
“…This surgical approach may have contributed to the high success rate of the implants. It has been suggested that for the long-term success of a surgical protocol involving the immediate placement a bone augmentation technique with the use of an osteoconductive bone substitute is necessary, as is a resorbable membrane to prevent an extensive bone remodeling of the edentulous ridge [ 39 , 40 ]. Alveolar ridge volume has been improved with the use of different bone substitutes (allografts, xenografts, alloplastics) demonstrating a limited vertical bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In implant-supported fixed prosthetics, dental implants can support individual dental crowns in cases of single-tooth absence [ 15 ] or contribute to the construction of fixed-full arch prostheses [ 16 ]. The materials used for designing implant-supported restorations are continually evolving.…”
Section: Introductionmentioning
confidence: 99%